Demonstration of the Binding of 131 l-Metalodobenzylguanidine to Structures on the Plasma Membrane of Neuroblastoma Cell Lines - Busse, E.; Baum, R. P.; Hör, G.; Kornhuber, B. (Nuklearmedizin - NuclearMedicine, 1988)
In vitro studies of tumor tissue have shown that131 I-l BG is specifically bound to the plasma membrane-enriched fraction of two neuroblastoma cell lines (NA-2 and C-1300). NB C-1300 showed a slightly higher binding capacity than NB NA-2. It may be inferred from experiments performed with activators of the adrenergic and dopaminergic systems that binding of IBG to proteins on the plasma membrane which is physiologically important for binding of this guanidine derivative, is probable.